Rousseaujeva kurtizana s plemenitim srcem - predhodnica Dame s kamelijami - Bogataj-Gradišnik, Katarina (Primerjalna književnost, 2012)
This article seeks to identify the origins and individual elements of the myth of the noble courtesan in the eighteenth-century sentimental tradition. The study focuses on the episodic story about the love between the English lord and the Italian courtesan in Rousseau's novel The New Heloise.
Keywords: Rousseau, Jean-Jacques, 1712-1778; Prévost, Antoine François, 1697-1763; Richardson, Samuel, 1689-1761; francoska književnost; French literature; angleška književnost; 18. st.; sentimentalni romani; literarni liki; kurtizana